Research of beer quality with the addition of elder sap - Сидор, Василь Михайлович; Кошова, Валентина Миколаївна; Боярська, Ольга Василівна; Лавна, Марія Ігорівна (Technology audit and production reserves, 2015)
Today, beer production is aimed at developing and implementing a new range of products using new raw material, which gives it a certain flavor characteristics and increases the demand for products. In addition, the beer produced using non-traditional raw material has advantages: functional directed action, improved organoleptic and physical and chemical properties, longer shelf life. That is why work is devoted to the possibility of using the sap of black elderberry Sambucus nigra to make beer that promote the formation of a new range of products, to achieve the necessary organoleptic characteristics of the finished beer. Based on theoretical and experimental studies it is established the optimal dose of elder sap for beer production, the basic physical and chemical characteristics and organoleptic properties of the finished beer.